Middle-Income Transitions: Trap or Myth? - Jesus Felipe; Utsav Kumar; Reynold Galope (Asian Development Bank (ADB), 2014)
During the last few years, the newly coined term middle-income trap has been widely used by policymakers to refer to the middle-income economies that seem to be stuck in the middle-income range. However, there is no accepted definition of the term in the literature. In this paper, we study historical transitions across income groups to see whether there is any evidence that supports the claim that economies do not advance. Overall, the data rejects this proposition. Instead, we argue that what distinguishes economies in their transition from middle to high income is fast versus slow transitions. We find that, historically, it has taken a "typical" economy 55 years to graduate from lower-middle income (2,000 in 1990 purchasing power parity [PPP] ) to upper-middle income (7,250 in 1990 PPP ). Likewise, we find that, historically, it has taken 15 years for an economy to graduate from upper-middle income to high income (above 11,750 in 1990 PPP ). Our analysis implies that as of 2013, there were 10 (out of 39) lower-middle-income economies and that 4 (out of 15) upper-middle-income economies that were experiencing slow transitions (i.e., above 55 and 15 years, respectively). The historical evidence presented in this paper indicates that economies move up across income groups. Analyzing a large sample of economies over many decades, indicates that experiences are wide, including many economies that today are high income that spent many decades traversing the middle-income segment.
hdl:11540/4217
Keywords: O10; O40; 330; middle-income trap; middle-income transition; Entwicklung; Entwicklungsländer; Entwicklungstheorie